Intralesional triamcinolone for inflammatory acne: a comparative study of dose efficacy and investigation of a novel injection assistance device to enable self-administration of intralesional therapy - Lyra B. Olson; Callie M. Roberts; Sunil S. Dhawan; Ann Mazor Reed; Eduardo Weiss; Martin Zaiac; Justin M. Ko; Arash Mostaghimi (Journal of Dermatological Treatment)
Background Acne is the most common dermatologic condition in the U.S., but few treatments work for individual lesions. One effective spot treatment is an injection of low dose steroid into the inflammatory lesion by a dermatologist or other provider. However, this treatment is not readily available to most patients given limited access to timely in-office injections.Objective First, to evaluate the safety and efficacy of intralesional triamcinolone injection for inflammatory acne delivered by via self-injection with a novel injection assistance device versus standard provider-delivered intralesional injection. Second, to compare efficacy and safety of intralesional triamcinolone acetonide at 0.1% versus 0.2%.Methods Three sequentially enrolling, open label arms of study were performed across two clinical trials (NCT06170593, NCT06186596). The first two arms compared standard provider injections to device-assisted patient-administered injections of 0.1% triamcinolone into inflammatory acne lesions. A third arm was enrolled to compare efficacy of 0.1% vs. 0.2% triamcinolone delivered via self-injections as assessed by patient-reported outcomes.Results Patient-administered injections showed comparable safety and efficacy to provider-administered injections. Patients with more severe lesions reported improved lesion resolution at the higher 0.2% triamcinolone dose. There were no adverse events in any group.Conclusion This study supports the feasibility of self-administered, provider-prescribed intralesional treatments for inflammatory acne. Home administration could expedite lesion resolution and reduce scarring risk.